Dampak Oksidasi Protein oleh Sistim Oksidasi 2, 2’-azobis (2 amidipropane) dyhidrochloride (AAPH) dan Sistim Katalis Logam CuSO4 / H2O2 terhadap Komposisi Asam Amino Protein Daging Merah dan Putih Ikan Tongkol Putih - Daniel A.N. Apituley; Zuheid Noor; Purnama Darmadji; Suparmo Suparmo (agriTECH, 2006)
Protein endured oxidative damage from oxygen radicals in 2,2’azobis (2 amidipropane) dyhidrochloride (AAPH) and catalysts CuSO4/H2O2 oxidation systems. Indications of oxidation could be seen in the development of carbonyl protein and other more reactive substances such as protein peroxide, denaturation of the protein, as well as damages on the amino acids constituents of the protein such as hystidine, arginine, tyrosine, metionine, cysteine and tryptophane. The research was aimed to study the effect of oxygen radicals exposure in AAPH and catalysts CuSO4/H2O2 oxidation systems on amino acid content of Thunus sp fish meat proteins. Result indicated that histamine, arginine, tyrosine, methionine, and phenylalanine amino acids in red meat undergone substantial reductions of 52.24%, 23.29%, 42.34%,22.22%, and 6.77% in AAPH system, and 12.34%, 27.59%,31.95%, 23.39%, and 13.02% in catalyst CuSO4/H2O2oxidation system, respectively. While milder reduction of those amino acids in white meat of 48.21%, 9.12%, 15.31%, 38.22%, and 22.44% in AAPH system, and 8.43%, 3.85%, 10.88%, 24.05%, and 57.25% in catalyst system, respectively.  It was obvious that red meat undergone more damages in both oxidation systems compared to the white meat counterpart.